Komparasi Risiko Produksi dan Kelayakan Usahatani Padi Sawah Tadah Hujan Sulawesi Selatan - Arifin, Arifin; Syafiuddin, Syafiuddin; Zulkifli, Zulkifli; Nurdin, Nurdin; Asriyani, Asriyani; Megawati, Megawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
An agricultural business is a business that is always characterized by variability in results or high risk. Good farming must be supported by farmers' income by looking at the ratio of income to farming costs incurred. This research aims to analyze the comparative risk of production, income, and feasibility of rainfed lowland rice farming. The research was conducted in Maros Regency, namely Minasa Baji Village, Bantimurung District, and Bonto Cabu Village, Lau District. Meanwhile, Barru Regency is Sape'e Village, Barru District and Lempang Village, Tanete Riaja District. This research was carried out in April - March 2023. The population of this study were all farmers who cultivated rice in rainfed rice fields at the research location. The total population is 1,259 farmers, consisting of 634 in Maros Regency and 544 in Pangkajene Islands Regency. The number of respondents was 100 farmers. The sample was selected using the proportional random sampling method. The data collection techniques used were observations and interviews. Data were analyzed using quantitative descriptive techniques with the independent sample t-test. The research results show that farmers are at risk in terms of production in Maros Regency and Barru Regency. The results of the t-test analysis showed no differences in production risk at the two locations. The income earned by Maros Regency is greater than Barru Regency. The results of the t-test analysis show differences in income from the two districts. Maros Regency's income is IDR 6,405,167.20 and Barru Regency's income is IDR 6,055,875.06. Rainfed lowland rice farming in Maros Regency and Barru Regency is worth pursuing. The results of the t-test analysis show a difference, namely that the feasibility of Maros Regency is greater than that of Barru Regency. Maros Regency has a feasibility value of 2.25 and Barru Regency is 2.07.